Analysis of the Relationship between Moral Judgment Competences and Empathic Skills of University Students - Aridag, Nermin Ciftci; Yuksel, Asuman (EDAM, 2010)
The aim of this study is to analyse whether there is a significant relationship between moral judgment competence and empathic skills of the students studying at Uludag University. In this article, the results of two researches carried out on two different samples are presented. In the first research, data were collected using David's Interpersonal Reactivity Index (IRI) and Lind's Moral Judgment Test (MJT) and the participants were 68 female and 61 male students between the ages of 20 and 29 (average: 22.85) who are studying in different departments in the Faculty of Education at Uludag University. The second research was conducted on 294 female and 141 male students between the ages of 18 and 30 (average: 22.30) who are studying in different faculties of Uludag University. Data were gathered by using Dokmen's Empathic Skill Scale (ESS) and Lind's Moral Judgment Test (MJT). In the two separate studies there was no significant relationship between students' moral test points and their general empathy points. The analysis of the relationship between the moral judgment test points of students whose Interpersonal Reactivity Index (IRI) points are between the top and bottom 27 percent segments revealed a significant negative relationship (r=.45.6; p>0.01) between the points students got from the 'personal distress' subscale and the ones they got from the 'workers' dilemma' subscale of the moral judgment test. Data were discussed in accordance with the relevant literature that focuses on the relationship between moral judgment and empathy.
Keywords: Moral Judgment Competence; Moral Development; Empathy; University Students; PROSOCIAL DEVELOPMENT; EMOTIONAL DOG; MODEL; COGNITION; BEHAVIOR; Education & Educational Research